ANALISIS MANAJEMEN OPERASIONAL PADA STANDAR PROSEDUR CV. ADHI JAYA CONSULTANT - Ade Jakaria; Dessy isfianadewi (Jurnal Bina Manajemen, 2022)
This study aims to analyze the application of Standard Operating Procedures on CV. Adhi Jaya Consultant. This study uses a qualitative approach and data collection methods in the form of observation, interviews and documentation. Results regarding the implementation of the seven main points in Standard Operating Procedures. (1) efficiency, there is still waste in terms of working time. (2) consistent, in the implementation of employees it is quite consistent to be guided by the existing SOPs. (3) minimizing errors, training is carried out before carrying out the work. (4) problem solving, the existing SOPs are detailed enough to find the root of the problem if there is a lack of data, but the SOP does not contain sanctions, problem solving, termination of employment and conflict resolution. (5) labor protection, the existing SOP already regulates work safety for employees in the field, but the SOP does not contain detailed rules regarding social security and compensation for employees. (6) work map, the existing SOP only regulates the workflow, where an executor is accompanied by several assistants in their work. (7) defense limits, monitoring carried out every month by the relevant agencies to find out whether the progress of project implementation is in accordance with existing SOPs or not